Whole-Genome Sequencing and Molecular Analysis of Ceftazidime-Avibactam-Resistant KPC-Producing Klebsiella pneumoniae from Intestinal Colonization in Elderly Patients - Giulia Errico; Maria Del Grosso; Michela Pagnotta; Manuela Marra; Maria Carollo; Marina Cerquetti; Elena Fogato; Elisabetta Cesana; Flaminia Gentiloni Silverj; Dorjan Zabzuni; Angelo Rossini; Annalisa Pantosti; et al. (MDPI AG, 2023)
Ceftazidime-avibactam (CAZ-AVI) is an active antibiotic combination of a β-lactam-β-lactamase inhibitor against carbapenemase-producing Enterobacterales. Reports of resistance to CAZ-AVI other than metallo-β-lactamases have increased in recent years. The aim of this study was to analyze KPC-Klebsiella pneumoniae (KP) isolates resistant to CAZ-AVI from the intestinal carriage of hospitalized elderly patients in Italy, in February 2018-January 2020. Characterization of CAZ-AVI-resistant KP isolates, including MLST, resistome, virulome and plasmid content, was performed by WGS analysis. Out of six CAZ-AVI-resistant KP isolates, three belonged to ST101 and three to ST512; two isolates produced KPC-3 (both ST512), four had mutated KPC-3 (KPC-31, in ST101 and ST512, and KPC-46, both ST101). All CAZ-AVI-resistant KP isolates were multidrug-resistant and carried several resistance genes. The yersiniabactin ybt9 gene cluster was present in all ST101 isolates, while, in ST512 isolates, no virulence genes were detected. Several plasmids were detected: IncF was present in all isolates, as well as IncR and Col440 in ST101 and IncX3 in ST512 isolates. In conclusion, it is important to monitor the circulation of K. pneumoniae resistant to CAZ-AVI to prevent the spread of clones causing difficult-to-treat infections. The presence of mutated KPC-3 in high-risk K. pneumoniae clones resistant to CAZ-AVI in hospitalized patients deserves attention.